2022
DOI: 10.1210/clinem/dgac466
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Diagnosis of Noninvasive Follicular Thyroid Neoplasm with Papillary-like Nuclear Features

Abstract: Context Noninvasive encapsulated follicular variant of papillary thyroid cancer (EFVPTC) was reclassified as noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) in January 2017. The impact of this nomenclature change at a population level remains unknown. Objective Examine use of NIFTP across different US regions and populations. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…This may be attributed to our institutional practices, as demonstrated in our previous study by Gajzer et al ., in which we reported a higher prevalence of NIFTPs in aspirates with cytologic atypia in BIII 6 . Based on surgical resections diagnosed between 2018 and 2022, our institution's rate of NIFTP is approximately 3% (65 of 1991 lobectomy/thyroidectomy cases), comparable with findings from other studies 25, 26 . This observation emphasizes the critical role of considering institutional practices and previous studies when interpreting and comparing results.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This may be attributed to our institutional practices, as demonstrated in our previous study by Gajzer et al ., in which we reported a higher prevalence of NIFTPs in aspirates with cytologic atypia in BIII 6 . Based on surgical resections diagnosed between 2018 and 2022, our institution's rate of NIFTP is approximately 3% (65 of 1991 lobectomy/thyroidectomy cases), comparable with findings from other studies 25, 26 . This observation emphasizes the critical role of considering institutional practices and previous studies when interpreting and comparing results.…”
Section: Discussionsupporting
confidence: 80%
“…6 Based on surgical resections diagnosed between 2018 and 2022, our institution's rate of NIFTP is approximately 3% (65 of 1991 lobectomy/thyroidectomy cases), comparable with findings from other studies. 25,26 This observation emphasizes the critical role of considering institutional practices and previous studies when interpreting and comparing results. By acknowledging the influence of institutional practices, we can better evaluate the significance and generalizability of our findings.…”
Section: Discussionmentioning
confidence: 86%
“…2.2% to 2.6% of thyroid cancers in 2018-2019 vs. 18.6% of PTC estimated by EPS. 50 These data suggest that the impact of NIFTP is not as considerable as initially estimated, and variations in incidence may be a result of variation of cancer rates in different populations, and/or variations in the interpretation of PTC nuclear atypia, which is still subjective despite efforts to objectify it. 51 Therefore, each center should consider basing their clinical decisions on their own data, including incidence of NIFTP in their patient population, and their thresholds for diagnosing PTC.…”
Section: Discussionmentioning
confidence: 79%
“…A comprehensive metanalysis found that worldwide incidence of NIFTP (6% of PTC) is much lower than initially estimated, and significantly lower in Asian countries (2.1%) compared with Western countries (9.3%–9.6%) 49 . A recently published epidemiology study using SEER‐22 data, by Chen et al., reported that NIFTP comprised a small fraction of previously diagnosed thyroid cancers, which was significantly less than was anticipated by EPS: 2.2% to 2.6% of thyroid cancers in 2018–2019 vs. 18.6% of PTC estimated by EPS 50 . These data suggest that the impact of NIFTP is not as considerable as initially estimated, and variations in incidence may be a result of variation of cancer rates in different populations, and/or variations in the interpretation of PTC nuclear atypia, which is still subjective despite efforts to objectify it 51 .…”
Section: Discussionmentioning
confidence: 95%